Efficacy of lelli test for detecting anterior cruciate ligament tear - Dhakal, Binit; Gurung, S; Rijal, B; Adhikari, Bhoj Raj (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Anterior cruciate ligament is most commonly injured knee ligament which may be stretched, partially torn, or completely torn. Commonly applied tests in clinical practice to determine Anterior cruciate ligament injuries are the anterior drawer test, the Lachman, and the pivot shift test. This study is aimed to establish efficacy of Lelli test in diagnosing ACL tear in relation to MRI or arthroscopic finding.METHODS: Prospective observational study performed in National Trauma Centre and Civil Hospital, Kathmandu. This study evaluated 90 consecutive patients seen at OPD for 1 year. All patients with a chief concern of acute knee pain following trauma, popping sound, swelling, instability, who underwent physical examination and MRI and necessary arthroscopic procedure.RESULTS: Average subject age was 30 years among which 56 were males and 34 were females. Eighty (88.8%) had Anterior cruciate ligament tears diagnosed by magnetic resonance imaging and confirmed by arthroscopy. The sensitivity and specificity of Lelli test were 87.5%, 93.2%respectively as compared to that of Anterior drawer test (81.2%, 90.5%), Lachman test (93.8%, 90.5%), pivot shift test (87.5%, 62.2%).CONCLUSION: The Lelli test showed high sensitivity, specificity, in the detection of anterior cruciate ligament tear comparable to other Lachman, anterior drawer test, or pivot shift tests. It can be done in case where other test couldn’t be done due to pain, also Lelli test eliminates drawback of other tests. It should be regularly performed along with other tests